Frequency of Diabetes Mellitus, Impaired Oral Glucose Tolerance Test, Hepatitis B Surface Antibody (HCV Ab) in Saudi Population Undergoing Cataract Surgery - Adnan Qadir, Khawaja Khalid Shoaib, Amjad Ali Khan (Pakistan Journal of Ophthalmology, 2008)
Purpose: To assess the frequency of diabetes mellitus and serological markers of viral hepatitis in Saudi Arabian patients undergoing cataract surgery. Material and Methods: The medical records of all the patients who had undergone cataract surgery during the two years period extending from 2002 to 2003 at the ophthalmology unit of Najran Armed Forces Hospital Programme (NAFHP), Kingdom of Saudi Arabia (KSA) were retrieved and records of 80 randomly selected patients were analyzed to find the frequency of diabetes mellitus (DM), impaired oral glucose tolerance test (IGT), hepatitis B surface Antigen (HBsAg) and antibody to hepatitis C (anti HCV). Results: The patients ranged in age from 44 to 93 years (mean: 72 years). They comprised of 45 males and 35 females. 12.5% patients were having IGT while 25% patients were diabetic. Of all the diabetic patients, 70% were known diabetics whereas 30% were newly diagnosed. HBsAg was present in 2.5% of patients whereas HCV Ab was detectable in 5.2% of cases. Conclusion: Cataract patients should undergo preoperative laboratory investigations to reveal any undiagnosed prevalent conditions like DM/IGT and viral hepatitis, as hyperglycemia is a known etiological factor for infections and affects wound healing, whereas viral hepatitis can be transmitted to the surgeon or the paramedical staff.